A Review on Reproductive Biology and Breeding System in Melia dubia Cav. - Mohapatra, Sourav Ranjan; Singh, Poonam; Rana, Anchal; Kumar, Ashok (Indian Forester, 2021)
A prime member of family Meliaceae, Melia dubia (Cav. Syn. Melia composita Willd.) is a multipurpose tree species with global significance. Although species bears versatile importance world over, information on reproductive biology and breeding system is scarce and limited. The initiation of advance generation breeding in Melia dubia needs special focus on floral morphology, biology and breeding system aspects. Therefore, a systematic review on reproductive biology of Melia dubia was conducted and has been presented in this paper. It reveals that species bears complex hermaphrodite flower with maximum flowering during mid of March. Though information on reproductive biology is extremely inadequate, anthesis occurs during morning hours and stigma attains receptivity two hours prior to that and continues upto twelve hours of anthesis. Information on pollination biology and breeding system of Melia dubia revealed predominance of self pollination and self compatibility with frequent visiting of insects during flowering. Hybridization activities in M. dubia have not yet been reported and need to be envisaged for further improvement of species.